Parenthood, child care, and nonstandard work schedules in Europe - Mareike Bünning; Matthias Pollmann-Schult (European Societies, 2016)
An increasing proportion of the European labor force works in the evening, at night or on weekends. Because nonstandard work schedules are associated with a number of negative outcomes for families and children, parents may seek to avoid such schedules. However, for parents with insufficient access to formal child care, working nonstandard hours or days may be an adaptive strategy used to manage child-care needs. It enables `split-shift' parenting, where parents work alternate schedules, allowing one of the two to be at home looking after the children. This study examines the prevalence of nonstandard work schedules among parents and nonparents in 22 European countries. Specifically, we ask whether the provision of formal child care influences the extent to which parents of preschool-aged children work nonstandard schedules. Using data from the European Social Survey and multilevel models, we find evidence that the availability of formal child care reduces nonstandard work among parents. This indicates that access to formal child care enables parents to work standard schedules. To the extent that nonstandard work schedules are negatively associated with child well-being, access to formal child care protects children from the adverse effects of their parents' evening and night work.
Keywords: 330; nonstandard schedules; parenthood; child care